Portable 3D-printed system for on-site MDMA electrochemical detection - Elisa D. Bottelli; Larissa M.A. Melo; Maxwell D. Bridges; Jason Boes; Thaisa A. Baldo; Lucas F. de Lima; Wendell K.T. Coltro; Luciano C. Arantes; William R. de Araujo; Charles S. Henry (Analytica Chimica Acta, 2026)

An integrated in-situ coordination strategy enabling high-performance layered cathodes for sodium-ion batteries - Hongyi Wang; Zixuan Huang; Craig A. Bridges; Cheng Li; Zhi Long; Shilong Li; Kai Liu; Shiqiang Liu; Qingqing Zhang; Sung-Soo Kim; Xiao-Guang Sun; Lianqi Zhang; et al. (Chemical Engineering Journal, 2026)

Floating treatment wetlands for brackish ponds: plant salinity tolerance evaluation - Clare Entwistle; Sarah A. White; Amy E. Scaroni; Debabrata Sahoo; William C. Bridges (Hydrobiologia, 2026)
Floating treatment wetlands (FTWs) enhance the nutrient removal efficiency of ponds. However, most FTW research has focused on freshwater applications, with little plant selection guidance for ponds along the salinity gradients that are common in coastal regions. Salinity can damage or kill the typical freshwater plants used in FTWs, decreasing overall nutrient removal efficacy and important aesthetic value. Four greenhouse studies were performed to assess the performance of 11 native aquatic macrophytes under salinity regimes that span oligohaline and mesohaline conditions. After the 8-week experimental period, Canna flaccida Salisb, and Verbena hastata L. were not salt-tolerant and did not survive in salinity exposures above 0.5 g l −1 . Phyla nodiflora (L.) Greene demonstrated low salt tolerance (< 5 g l −1 ). Crinum americanum L., Kosteletzkya virginica (L.) C. Presl ex. Al. Gray, Bacopa monnieri L., and Uniola paniculata L. were moderately salt-tolerant, surviving with salinity exposures < 10 g l −1 . Solidago sempervirens L. , Spartina patens (Aiton) Muhl., Sporobolus virginicus (L.) Kunth, and Borrichia frutescens (L.) DC. were the most salt-tolerant and showed minimal signs of stress (mean visual stress scores above 3) in salinity exposure scenarios up to 18 g l −1 . Plants were more compact in growth habit with higher salinity exposures. Results from this study provide a baseline for practitioners detailing plants that may be suitable for installation in FTWs deployed in brackish ponds.

Multi-scale use of cleaning stations by manta rays in Mozambique: Insights from remote underwater video surveillance - Jule Buschmann; Awantha Dissanayake; Jaime S. Davies; Amelia Bridges; Jennifer A. Keeping (Marine Environmental Research, 2026)

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

Long-term shifts in the spatial distribution of Common Cranes Grus grus - Morgane Gicquel; Lovisa Nilsson; Juan C. Alonso; Matthew Low; Javier A. Alonso; Dmitrijs Boiko; Damon Bridge; Patrick Dulau; Thomas Heinicke; Anne Kettner; Yosef Kiat; Petras Kurlavičius; et al. (Journal of Ornithology, 2026)
Migratory bird distributions are inherently dynamic and vary with seasons, but are also increasingly influenced by climate and land-use changes. Understanding these shifts is crucial for interpreting ecosystem dynamics and guiding future conservation efforts. In this study, we analysed 187,779 resightings (1985–2021) of 5,120 colour-banded Common Cranes ( Grus grus ), originating from 8 northern European countries, to examine long-term spatiotemporal distribution dynamics along the Western and Central European flyways. Our results show that the flyway use has remained largely consistent with the previous studies: most cranes follow the Western European flyway, wintering in France and Spain, whilst a smaller proportion follow the Central European flyway, wintering in Hungary and occasionally reaching Israel and North Africa. However, we also observed a pronounced northward shift in wintering distribution over the past 4 decades. At the same time, breeding distributions showed a slight southward expansion, potentially reflecting both population growth and changes in marking effort. Our results demonstrate the importance of long-term monitoring in detecting range shifts and highlight the need for adaptive conservation planning in the face of accelerating climate and land-use change.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

OS02-09 Skin sensitization potency assessment of fragrance chemicals for quantitative risk assessment – comparing in vivopotency values to the point-of-departure derived with new approach methodologies - A. Natsch; A. Irizar; P. Griem; J. Bridges; H.J. Bender; M. Vey; I. Lee; A.M. Api; P. Kern; I. Kimber (Toxicology Letters, 2025)

Unveiling the potential of calcium chloride for Botrytis blight management in cut roses using untargeted metabolomics analysis - Melissa Muñoz; William C. Bridges; Christopher A. Saski; Guido Schnabel; James E. Faust (Postharvest Biology and Technology, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

A novel approach to metabolic profiling in case models of MECP2-related disorders - Jessica A. Cooley Coleman; Bridgette A. Moffitt; William C. Bridges; Kelly Jones; Melanie May; Cindy Skinner; Michael J. Friez; Steven A. Skinner; Charles E. Schwartz; Luigi Boccuto (Metabolic Brain Disease, 2025)
Genetic abnormalities of the MECP2 gene cause several conditions grouped under the umbrella term of MECP2 -related disorders and characterized by a variety of phenotypes. We applied a functional approach to identify metabolic profiles in two patients with Rett syndrome (RTT) and one patient with MECP2 duplication syndrome (MRXSL). Such an approach is based on the Phenotype Mammalian Microarray (PM-M) technology, which is designed to assess the cellular production of energy in the presence of different compounds generating distinct metabolic environments. The findings in the three case models were compared versus 50 controls. Although the small number of samples prevented most results from reaching significant p -values when adjusted with the Benjamini-Hochberg correction, some interesting trends emerged. Some compounds indicated metabolic trends shared by the two conditions, like increased energy production in the presence of energy sources such as pectin, adenosine, and pyruvic acid, or decreased metabolic response to certain hormones. Other compounds showed opposite trends for the two disorders, like interleukin-1 beta (IL-1 beta), which caused decreased energy production in the RTT group but increased energy production in the patient with MRXSL. The response to IL-1 beta also offers valuable insights into the pathogenic mechanism and potential therapeutic approaches. The metabolic profiling of MECP2 -related disorders bears a remarkable translational potential since it may be helpful to investigate the molecular abnormalities underlying the phenotypical variety in this spectrum of conditions, develop biomarkers for the identification of ideal candidates for treatments like the recently approved trofenatide, and identify potential targets for the development of novel therapeutic approaches.

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

The structure of a catalytically inactive Paracoccus denitrificans complex I mutant under turnover conditions - Robert A. Waddell; Owen D. Jarman; Bozhidar S. Ivanov; Hannah R. Bridges; Judy Hirst (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

A generalized, model-free framework for assessing scour-induced bridge pier instability - Neandro DeMello; Jennifer A. Bridge (Engineering Structures, 2024)

Spatiotemporal variation in cognitive phenotype, social network position, and distribution of social associations in a food-caching bird - A. M. Pitera; V. K. Heinen; J. F. Welklin; C. L. Branch; B. R. Sonnenberg; L. M. Benedict; E. S. Bridge; V. V. Pravosudov (Behavioral Ecology and Sociobiology, 2024)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Sexually concordant and dimorphic transcriptional responses to maternal trichloroethylene and/or N-acetyl cysteine exposure in Wistar rat placental tissue - Elana R. Elkin; Anthony L. Su; John F. Dou; Justin A. Colacino; Dave Bridges; Vasantha Padmanabhan; Sean M. Harris; Erica Boldenow; Rita Loch-Caruso; Kelly M. Bakulski (Toxicology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Depth and latitudinal gradients of diversity in seamount benthic communities - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Journal of Biogeography, 2022)
Aim Latitudinal and bathymetric species diversity gradients in the deep sea have been identified, but studies have rarely considered these gradients across hard substratum habitats, such as seamount and oceanic island margins. This study aimed to identify whether the current understanding of latitudinal and bathymetric gradients in α‐diversity (species richness) apply to seamount ecosystems, as well as ascertaining whether identifiable trends were present in seamount β‐diversity along a bathymetric gradient. Location Exclusive Economic Zones of Saint Helena, Ascension Island and Tristan da Cunha, spanning 8–40°S in the South Atlantic. Taxon Seamount megabenthic communities. Methods Images from 39 transects, collected between 250 and 950 m, were used to characterise species richness. We subsequently applied general linear models to test possible environmental drivers across latitudinal and bathymetric ranges. Regression models were employed to investigate the β‐diversity gradient of species turnover with depth. Results Transects in temperate latitude had significantly higher species richness than those in the tropics. Surface primary productivity and substrate hardness both had significant positive effects on species richness, and a weak relationship between temperature and species richness was observed. No significant relationship between species richness and depth was detected, but there was significant species turnover with depth. Main conclusions Seamounts and oceanic islands do not conform to established depth–diversity relationships within the depth range studied. However, seamounts and oceanic islands in the South Atlantic do appear to follow a parabolic latitudinal diversity gradient, closely associated with higher productivity in temperate regions.

A critical review of citrulline malate supplementation and exercise performance - Lewis A. Gough; S. Andy Sparks; Lars R. McNaughton; Matthew F. Higgins; Josh W. Newbury; Eric Trexler; Mark A. Faghy; Craig A. Bridge (European Journal of Applied Physiology, 2021)
As a nitric oxide (NO) enhancer, citrulline malate (CM) has recently been touted as a potential ergogenic aid to both resistance and high-intensity exercise performance, as well as the recovery of muscular performance. The mechanism has been associated with enhanced blood flow to active musculature, however, it might be more far-reaching as either ammonia homeostasis could be improved, or ATP production could be increased via greater availability of malate. Moreover, CM might improve muscle recovery via increased nutrient delivery and/or removal of waste products. To date, a single acute 8 g dose of CM on either resistance exercise performance or cycling has been the most common approach, which has produced equivocal results. This makes the effectiveness of CM to improve exercise performance difficult to determine. Reasons for the disparity in conclusions seem to be due to methodological discrepancies such as the testing protocols and the associated test–retest reliability, dosing strategy (i.e., amount and timing), and the recent discovery of quality control issues with some manufacturers stated (i.e., citrulline:malate ratios). Further exploration of the optimal dose is therefore required including quantification of the bioavailability of NO, citrulline, and malate following ingestion of a range of CM doses. Similarly, further well-controlled studies using highly repeatable exercise protocols with a large aerobic component are required to assess the mechanisms associated with this supplement appropriately. Until such studies are completed, the efficacy of CM supplementation to improve exercise performance remains ambiguous.

Human primary visual cortex shows larger population receptive fields for binocular disparity-defined stimuli - Ivan Alvarez; Samuel A. Hurley; Andrew J. Parker; Holly Bridge (Brain Structure and Function, 2021)
The visual perception of 3D depth is underpinned by the brain’s ability to combine signals from the left and right eyes to produce a neural representation of binocular disparity for perception and behaviour. Electrophysiological studies of binocular disparity over the past 2 decades have investigated the computational role of neurons in area V1 for binocular combination, while more recent neuroimaging investigations have focused on identifying specific roles for different extrastriate visual areas in depth perception. Here we investigate the population receptive field properties of neural responses to binocular information in striate and extrastriate cortical visual areas using ultra-high field fMRI. We measured BOLD fMRI responses while participants viewed retinotopic mapping stimuli defined by different visual properties: contrast, luminance, motion, correlated and anti-correlated stereoscopic disparity. By fitting each condition with a population receptive field model, we compared quantitatively the size of the population receptive field for disparity-specific stimulation. We found larger population receptive fields for disparity compared with contrast and luminance in area V1, the first stage of binocular combination, which likely reflects the binocular integration zone, an interpretation supported by modelling of the binocular energy model. A similar pattern was found in region LOC, where it may reflect the role of disparity as a cue for 3D shape. These findings provide insight into the binocular receptive field properties underlying processing for human stereoscopic vision.

Benthic Assemblage Composition of South Atlantic Seamounts - Amelia E. H. Bridges; David K. A. Barnes; James B. Bell; Rebecca E. Ross; Kerry L. Howell (Frontiers in Marine Science, 2021)
Seamounts and oceanic islands rise from the seafloor and provide suitable habitat for a diverse range of biological assemblages including Vulnerable Marine Ecosystems (VMEs). Whilst they have been the focus of some work globally, there has been little description of the biological and physical environments of seamounts in the South Atlantic Ocean. In this study, we characterized benthic assemblage composition from 13 seamounts and oceanic islands spanning 8–40°S within the exclusive economic zones (EEZs) of Ascension Island, Saint Helena and Tristan da Cunha. Drop camera imagery was collected between 170 and 1000 m. All fauna present in images were identified and quantified, and multivariate statistics were used to describe biological assemblages and identify their environmental drivers. Benthic communities of temperate regions (Tristan da Cunha archipelago) were shown to be distinct from those found in the tropics, with latitude and depth identified as key environmental drivers of assemblage composition. Our results are consistent with the current understanding of the biogeography of the South Atlantic, both in terms of the distinction between tropical and temperate regions, and the influence of depth and water mass structure on assemblage distribution. Faunal assemblages are similar to those observed in the North Atlantic in terms of functional groups. VMEs are present within the EEZs of all three territories and are potentially protected from some threats by large marine protected areas (MPAs). Our imagery, data and analyses provide a baseline for south Atlantic seamounts so that future monitoring can establish whether existing protected status is sufficient to conserve both unique biodiversity and considerable potential for vital ecosystem services.

Transcriptional profiling of the response to the trichloroethylene metabolite S-(1,2-dichlorovinyl)-l-cysteine revealed activation of the eIF2α/ATF4 integrated stress response in two in vitro placental models - Elana R. Elkin; Kelly M. Bakulski; Justin A. Colacino; Dave Bridges; Brian A. Kilburn; D. Randall Armant; Rita Loch-Caruso (Archives of Toxicology, 2021)

Life History and Ecology of Bluenose Warehou (Hyperoglyphe antarctica, Centrolophidae) in the Southern Atlantic - James B. Bell; Vladimir Laptikhovsky; David K. A. Barnes; Ramon Benedet; Amelia E. Bridges; James Glass; Warren Glass; Rodney Green; Simon A. Morley; Simon Robertson; Georgia R. Robson; Harry Stanton; et al. (Frontiers in Marine Science, 2021)
Bluenose warehou ( Hyperoglyphe antarctica ) is a popular commercial fish in Australia and New Zealand, but its biology and ecology are very poorly known in other regions where it is found. We present here the first life history data for this species from the south Atlantic, focusing upon the exclusive economic zone (EEZ) of the United Kingdom Overseas Territory (UKOT) of Tristan da Cunha (TdC). Here, bluenose is known from several seamounts and island margins, typically occurring in waters between 200 and 1,000 m depth and is the target species of trawl and longline fishery operating since 1997. We use a suite of methods to describe important life history parameters, including length-weight and age-length relationships and size at recruitment, as well as examining commercial longline survey data to uncover habitat preferences of bluenose. This work has formed an important part of the United Kingdom government’s Blue Belt Program in TdC. It has underpinned the development of the first stock assessment for this species in the Atlantic, as well as a range of improved conservation measures for some of the more vulnerable species that occur in these areas, including seabirds and cold-water corals.

Multi‐hypothesis comparison of Farquhar and Collatz photosynthesis models reveals the unexpected influence of empirical assumptions at leaf and global scales - Anthony P. Walker; Abbey L. Johnson; Alistair Rogers; Jeremiah Anderson; Robert A. Bridges; Rosie A. Fisher; Dan Lu; Daniel M. Ricciuto; Shawn P. Serbin; Ming Ye (Global Change Biology, 2021)
Mechanistic photosynthesis models are at the heart of terrestrial biosphere models (TBMs) simulating the daily, monthly, annual and decadal rhythms of carbon assimilation ( A ). These models are founded on robust mathematical hypotheses that describe how A responds to changes in light and atmospheric CO 2 concentration. Two predominant photosynthesis models are in common usage: Farquhar (FvCB) and Collatz (CBGB). However, a detailed quantitative comparison of these two models has never been undertaken. In this study, we unify the FvCB and CBGB models to a common parameter set and use novel multi‐hypothesis methods (that account for both hypothesis and parameter variability) for process‐level sensitivity analysis. These models represent three key biological processes: carboxylation, electron transport, triose phosphate use (TPU) and an additional model process: limiting‐rate selection. Each of the four processes comprises 1–3 alternative hypotheses giving 12 possible individual models with a total of 14 parameters. To broaden inference, TBM simulations were run and novel, high‐resolution photosynthesis measurements were made. We show that parameters associated with carboxylation are the most influential parameters but also reveal the surprising and marked dominance of the limiting‐rate selection process (accounting for 57% of the variation in A vs. 22% for carboxylation). The limiting‐rate selection assumption proposed by CBGB smooths the transition between limiting rates and always reduces A below the minimum of all potentially limiting rates, by up to 25%, effectively imposing a fourth limitation on A . Evaluation of the CBGB smoothing function in three TBMs demonstrated a reduction in global A by 4%–10%, equivalent to 50%–160% of current annual fossil fuel emissions. This analysis reveals a surprising and previously unquantified influence of a process that has been integral to many TBMs for decades, highlighting the value of multi‐hypothesis methods.

Coral reef annihilation, persistence and recovery at Earth’s youngest volcanic island - P. F. Smallhorn-West; J. B. Garvin; D. A. Slayback; T. M. DeCarlo; S. E. Gordon; S. H. Fitzgerald; T. Halafihi; G. P. Jones; T. C. L. Bridge (Coral Reefs, 2020)

Elevation-related differences in annual survival of adult food-caching mountain chickadees are consistent with natural selection on spatial cognition - L. M. Benedict; A. M. Pitera; C. L. Branch; D. Y. Kozlovsky; B. R. Sonnenberg; E. S. Bridge; V. V. Pravosudov (Behavioral Ecology and Sociobiology, 2020)

Expression and Characterization of a Bright Far-red Fluorescent Protein from the Pink-Pigmented Tissues of Porites lobata - Mary C. Bridges; Cheryl M. Woodley; Esther C. Peters; Lisa A. May; Sylvia B. Galloway (Marine Biotechnology, 2020)

Shallow genetic population structure in an expanding migratory bird with high breeding site fidelity, the Western Eurasian Crane Grus grus grus - Martin Haase; Henriette Höltje; Beate Blahy; Damon Bridge; Eberhard Henne; Ulf S. Johansson; Katrin Kaldma; Ekaterina A. Khudyakova; Amy King; Aivar Leito; Wolfgang Mewes; Elena A. Mudrik; et al. (Journal of Ornithology, 2019)

Characterization of SNP markers for the painted bunting (Passerina ciris) and their relevance in population differentiation and genome evolution studies - Andrea Contina; Rachael A. Bay; Vinh Le Underwood; Thomas B. Smith; Jeffrey F. Kelly; Eli S. Bridge; Kristen C. Ruegg (Conservation Genetics Resources, 2019)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Multiple non-catalytic ADAMs are novel integrin α4 ligands - Lei Wang; Jason A. Hoggard; Erica D. Korleski; Gideon V. Long; Brandy C. Ree; Kenneth Hensley; Stephen R. Bond; Tyra G. Wolfsberg; JianMing Chen; Tonya N. Zeczycki; Lance C. Bridges (Molecular and Cellular Biochemistry, 2018)

Photo-induced toxicity in early life stage fiddler crab (Uca longisignalis) following exposure to Deepwater Horizon oil - Leigh M. Damare; Kristin N. Bridges; Matthew M. Alloy; Thomas E. Curran; Brianne K. Soulen; Heather P. Forth; Claire R. Lay; Jeffrey M. Morris; James A. Stoeckel; Aaron P. Roberts (Ecotoxicology, 2018)

A cloud-based spatial-temporal inventory for sustainable urban soil management - Latoisha Y. Green; Elena A. Mikhailova; Christopher J. Post; Christophe C. J. G. Darnault; William C. Bridges; Mark A. Schlautman (Urban Ecosystems, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Population development within the coffee wilt pathogen Gibberella xylarioides reflects host-related divergence - A. G. Buddie; J. Crozier; M. A. Rutherford; J. Flood; P. D. Bridge (European Journal of Plant Pathology, 2015)

Benthic community composition on submerged reefs in the central Great Barrier Reef - T. E. Roberts; J. M. Moloney; H. P. A. Sweatman; T. C. L. Bridge (Coral Reefs, 2015)

Depressive symptoms in chronic hepatitis C are associated with plasma apolipoprotein E deficiency - David A. Sheridan; S. H. Bridge; M. M. E. Crossey; D. J. Felmlee; H. C. Thomas; R. D. G. Neely; S. D. Taylor-Robinson; M. F. Bassendine (Metabolic Brain Disease, 2014)

Hepatic Transcriptome Profiles Differ Among Maturing Beef Heifers Supplemented with Inorganic, Organic, or Mixed (50 % Inorganic:50 % Organic) Forms of Dietary Selenium - James C. Matthews; Zhi Zhang; Jennifer D. Patterson; Phillip J. Bridges; Arnold J. Stromberg; J. A. Boling (Biological Trace Element Research, 2014)

Removal of Plant Pathogen Propagules from Irrigation Runoff using Slow Filtration Systems: Quantifying Physical and Biological Components - Elizabeth T. Nyberg; Sarah A. White; Steven N. Jeffers; William. C. Bridges (Water, Air, & Soil Pollution, 2014)

Symbiodinium diversity in the sea anemone Entacmaea quadricolor on the east Australian coast - S. Pontasch; A. Scott; R. Hill; T. Bridge; P. L. Fisher; S. K. Davy (Coral Reefs, 2014)

The heparan sulfate editing enzyme Sulf1 plays a novel role in zebrafish VegfA mediated arterial venous identity - Bushra Gorsi; Feng Liu; Xing Ma; Timothy J. A. Chico; Ashok Shrinivasan; Kenneth L. Kramer; Esther Bridges; Rui Monteiro; Adrian L. Harris; Roger Patient; Sally E. Stringer (Angiogenesis, 2014)

Do Hummocks Provide a Physiological Advantage to Even the Most Flood Tolerant of Tidal Freshwater Trees? - Jamie A. Duberstein; Ken W. Krauss; William H. Conner; William C. Bridges; Victor B. Shelburne (Wetlands, 2013)

Lipids and HCV - M. F. Bassendine; D. A. Sheridan; S. H. Bridge; D. J. Felmlee; R. D. G. Neely (Seminars in Immunopathology, 2013)

Abundance and diversity of anemonefishes and their host sea anemones at two mesophotic sites on the Great Barrier Reef, Australia - T. Bridge; A. Scott; D. Steinberg (Coral Reefs, 2012)

Developmental profile of storage reserve accumulation in soybean somatic embryos - Yan He; Tammie E. Young; Karen Rebecca Clark; Kathryn F. Kleppinger-Sparace; William C. Bridges; Salvatore A. Sparace (In Vitro Cellular & Developmental Biology - Plant, 2011)

A uniform fish consumption advisory protocol for the Ohio River - Jeff A. Thomas; LaNetta Alexander; Tom Barron; Frank Borsuk; C. Lee Bridges; Eric Eisiminger; Tom Hornshaw; Mylynda Shaskus; Janice Smithson; Jim Stahl; Bill Toomey (Environmental Monitoring and Assessment, 2011)

Topography, substratum and benthic macrofaunal relationships on a tropical mesophotic shelf margin, central Great Barrier Reef, Australia - T. C. L. Bridge; T. J. Done; R. J. Beaman; A. Friedman; S. B. Williams; O. Pizarro; J. M. Webster (Coral Reefs, 2011)

Climatic correlates of temporal demographic variation in the tropical hover wasp Liostenogaster flavolineata - A. L. Cronin; C. Bridge; J. Field (Insectes Sociaux, 2011)

Building Local Community Commitment to Wetlands Restoration: A Case Study of the Cache River Wetlands in Southern Illinois, USA - Mae A. Davenport; Christopher A. Bridges; Jean C. Mangun; Andrew D. Carver; Karl W. J. Williard; Elizabeth O. Jones (Environmental Management, 2010)

A histological investigation of the occurrence of non‐reproductive female bluefin tuna Thunnus thynnus in the Mediterranean Sea - R. Zupa; A. Corriero; M. Deflorio; N. Santamaria; D. Spedicato; C. Marano; M. Losurdo; C. R. Bridges; G. De Metrio (Journal of Fish Biology, 2009)
The presence of non‐reproductive Atlantic bluefin tuna Thunnus thynnus females in the Mediterranean Sea was investigated through histological analysis of the gonads. Three hundred and twenty‐six ovary samples were collected from adults captured at different locations in the Mediterranean Sea during the reproductive seasons between 1998 and 2008. Only three specimens were considered to be in a non‐reproductive state: two of them were in a reabsorbing state showing ovaries with early vitellogenic oocytes and extensive α and β atresia of vitellogenic follicles; the third showed gonads with perinucleolar oocytes and was considered to be in a resting state. The low occurrence of non‐reproductive individuals found in this study makes it unlikely that non‐reproductive individuals aggregate with reproductive ones during their migration towards spawning grounds. Further research is suggested in order to investigate the potential presence of non‐reproductive individuals on non‐spawning grounds during the reproductive season.

Effects of hypoxia on the energy status and nitrogen metabolism of African lungfish during aestivation in a mucus cocoon - A. M. Loong; S. F. Ang; W. P. Wong; H. O. Pörtner; C. Bock; R. Wittig; C. R. Bridges; S. F. Chew; Y. K. Ip (Journal of Comparative Physiology B, 2008)

Domain II Hairpin Structure in ITS1 Sequences as an Aid in Differentiating Recently Evolved Animal and Plant Pathogenic Fungi - P. D. Bridge; T. Schlitt; P. F. Cannon; A. G. Buddie; M. Baker; A. M. Borman (Mycopathologia, 2008)

Association of the coprophilous fungus Pirella circinans with an indigenous beetle on the sub-Antarctic Bird Island - P. D. Bridge; K. A. Hughes; J. O. Denton (Polar Biology, 2008)

Germ cell proliferation and apoptosis during different phases of swordfish ( Xiphias gladius L.) spermatogenetic cycle - A. Corriero; S. Desantis; C. R. Bridges; D. E. Kime; P. Megalofonou; N. Santamaria; F. Cirillo; G. Ventriglia; A. Di Summa; M. Deflorio; F. Campobasso; G. De Metrio (Journal of Fish Biology, 2007)
Seasonal changes of testicular activity of the swordfish Xiphias gladius and correlations of plasma levels of testosterone (T) and 11‐ketotestosterone (11‐KT) with proliferation and apoptosis of germ cells, determined, respectively, with monoclonal antibodies against proliferating cell nuclear antigen and terminal deoxynucleotidyl transferase‐mediated d’UTP nick end labelling, are described. Three phases of the reproductive cycle were found: active spermatogenic (May), spawning (June to July) and spent (August to September) stages. Germ cell proliferating activity was highest in May, decreased during June to July and remained stable during August to September. Apoptotic germ cells, primary spermatocytes and spermatogonia, were present in all the specimens analysed and were more abundant in May. The levels of 11‐KT in plasma were always higher than T and were highest in May, in concomitance with the maximum proliferation and apoptosis rate of germ cells.

Revealing gene transcription and translation initiation patterns in archaea, using an interactive clustering model - Xiu-Feng Wan; Susan M. Bridges; John A. Boyle (Extremophiles, 2004)

Influence of environmental temperature on exercise-induced inspiratory muscle fatigue - Lee M. Romer; Matthew W. Bridge; Alison K. McConnell; David A. Jones (European Journal of Applied Physiology, 2004)

Histological investigation on the ovarian cycle of the bluefin tuna in the western and central Mediterranean - A. Corriero; S. Desantis; M. Deflorio; F. Acone; C. R. Bridges; J. M. De la Serna; P. Megalofonou; G. De Metrio (Journal of Fish Biology, 2003)
The histological analysis of eastern Atlantic bluefin tuna Thunnus thynnus ovaries caught from February to September 1999–2000, made it possible to distinguish the presence of seven oocyte developmental stages and allowed the characterization of six time‐dependent ovary maturity stages. The ovaries of mature (fork length, L F ≥ 110 cm) bluefin tuna were non‐active from August (spent period) to March (quiescent period) when they contained only perinucleolar‐stage oocytes. Ovary development started in April to early May (recrudescent period) with the appearance of oocytes at the lipid stage. Vitellogenesis appeared in mid‐May (ripening period) and post‐vitellogenesis occurred in late May to mid‐June (pre‐spawning period). In late June to early July, hydrated oocytes, a sign of imminent spawning, were found only in specimens caught in Balearic waters. Females ranging between 100 and 110 cm L F , captured during the recrudescent and ripening periods, had the largest oocytes at the lipid stage, most of which were degenerating. An extensive vitellogenic atresia was observed in the ovaries of five females caught during the spawning period in non‐spawning areas.

Adrenal Corticotropin Hormone and Nestling Bald Eagle Corticosterone Levels - W. W. Bowerman; C. J. Mehne; D. A. Best; K. R. Refsal; S. Lombardini; W. C. Bridges (Bulletin of Environmental Contamination and Toxicology, 2002)

Wildfire Regime in the Boreal Forest and the Idea of Suppression and Fuel Buildup - E. A. Johnson; K. Miyanishi; S. R. J. Bridge (Conservation Biology, 2001)

Quantifying the 5-HT 1A agonist action of buspirone in man - Bridge M.; Marvin G.; Thompson C.; Sharma A.; Jones D.; Kendall M. (Psychopharmacology, 2001)

Study of the sexual maturity of female bluefin tuna: purification and partial characterization of vitellogenin and its use in an enzyme‐linked immunosorbent assay - V. Susca; A. Corriero; C. R. Bridges; G. De Metrio (Journal of Fish Biology, 2001)
Plasma steroid levels of female bluefin tuna (BFT) Thunnus thynnus rose from c. 1·5 ng ml −1 during the quiescent period (March) to c. 7 ng ml −1 during the ripening period (May). Testosterone (T) increased further to c. 8 ng ml −1 during the pre‐spawning period (June) while 17β‐oestradiol (E 2 ) began to decrease. In the post‐spawning period (August) steroid levels decreased to −1 . Vitellogenin (Vtg) plasma levels seemed to follow changes in E 2 , showing an increase from the quiescent period to the ripening period of c. 18 mg ml −1 , decreasing slightly before spawning, and then decreasing after spawning. The Vtg content in plasma showed a good correlation both with the plasma levels of E 2 and T and with the percentage of vitellogenic oocytes at different periods of the reproductive cycle. Thus the ELISA could be taken as validated. Immunohistochemical staining of ovaries with anti BFT‐Vtg serum demonstrated a high cross‐reactivity with yolk proteins allowing the identification of vitellogenic oocytes.

Comparison of rRNA genotype frequencies ofParmelia sulcata from long established and recolonizing sites following sulphur dioxide amelioration - A. Crespo; P. D. Bridge; D. L. Hawksworth; M. Grube; O. F. Cubero (Plant Systematics and Evolution, 1999)

Regulation of MMP-9 (92 kDa type IV collagenase/gelatinase B) expression in stromal cells of human giant cell tumor of bone - Velidi H. Rao; Rakesh K. Singh; Julia A. Bridge; James R. Neff; G. Bradley Schaefer; Duane C. Delimont; Christopher M. Dunn; Warren G Sanger; Bruce A. Buehler; Raymond Sawaya; Garth L. Nicolson; Jasti S. Rao (Clinical & Experimental Metastasis, 1997)

Culture of airway epithelial cells collected by a nasal brushing technique - Michael A. Bridges (In Vitro Cellular & Developmental Biology - Animal, 1997)

Molecular characterization of isolates of Metarhizium from locusts and grasshoppers - P. D. Bridge; C. Prior; J. Sagbohan; C. J. Lomer; M. Carey; A. Buddie (Biodiversity and Conservation, 1997)

The fluctuation test - B. A. Bridges (Archives of Toxicology, 1980)

The anaerobic decomposition of benzoic acid during methane fermentation - C. L. Keith; R. L. Bridges; L. R. Fina; K. L. Iverson; J. A. Cloran (Archives of Microbiology, 1978)

Potato notes - C. Tice; W. C. Edmundson; W. Stuart; Seymour Bridge; Glen Carter; A. G. Allen; Daniel Dean; H. H. Zimmerly; J. O. Milward (American Journal of Potato Research, 1924)